Inner Peace and Personal Identity. Reflections on the Unity of the Confessions - Kiesel, Dagmar (Editorial Uniagustiniana, 2019)
The division of the Confessions into an autobiographical part (book 1-10) and an exegetical part to Gen. 1-2: 3 (book 11-13) has raised questions with respect to their unity. While the view that the Confessions cannot be regarded as a unitary whole is now considered as a marginal position, there are various approaches to an integrating interpretation. This contribution elaborates on the proposal that the unity of the Confessions arises from their interpretation as a narrative identity construction of Augustine. The underlying meta-narrative in the Confessions is Augustine's own doctrine of grace and original sin, which he has worked out in Simpl., 1, 2, shortly before. In the Confessions, Augustine illustrates the effect of divine grace and the transformation of man from homo sub lege and homo sub gratia to homo in pace exemplarily on the basis of his own life story. This understanding is supported by the further thesis that Augustine himself deals extensively with the question of "personal identity" in the Confessions and perceives identity in the context of neoplatonic conceptions as an inner-soul unity and harmony, which he conceives as unitas, quies/requies, and pax. The source of this unity is the eternal, unchanging one God. In Augustine, pax also stands for the condition of spiritual balance and represents the Christianized version of epicurean ataraxia and stoic tranquillitas animi. In addition, the contribution shows the systematic interlinkage of the Augustinian concepts of pax, unitas, caritas, requies, beatitudo, utifrui, res mutabiles-res immutabiles, creatio-creatura, temporalia-aeterna, and peregrinatio.